HISTOCHEMICAL STUDIES OF THE SACCUS VASCULOSUS OF A FRESH WATER FISH ANABAS TESTUDINEUS - GUPTA, AMITA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1989)
Studies on the localisation of protein and glycogen in the saccus vasculosus of A. testudines were made Two types of coronet cells i, e light and dark were observed on the basis of protein accumulation. Both types of the cells of Saccus were rich in the glycogen content.